2017
DOI: 10.1007/s00438-017-1364-7
|View full text |Cite
|
Sign up to set email alerts
|

Systematic transcriptome-wide analysis of mRNA–miRNA interactions reveals the involvement of miR-142-5p and its target (FOXO3) in skeletal muscle growth in chickens

Abstract: The goal of this study was to perform a systematic transcriptome-wide analysis of mRNA-miRNA interactions and to identify candidates involved in the interplay between miRNAs and mRNAs that regulate chicken muscle growth. We used our previously published mRNA (GSE72424) and miRNA (GSE62971) deep sequencing data from two-tailed samples [i.e., the highest (h) and lowest (l) body weights] of Recessive White Rock (WRR) and Xinghua (XH) chickens to conduct integrative analyses of the miRNA-mRNA interactions involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…MTT. The results showed that the cell activity was reduced significantly after 4 h of hypoxia, and MiRNAs, known as small non-coding RNAs, play vital roles in many biological processes, regulate gene expressions at post-transcriptional level and interfere negatively with translation and RNA silencing [18]. Previous study [19] shows that miR-142-3p targets box 1, attenuating apoptosis of cardiomyocytes induced by H/R.…”
Section: Discussionmentioning
confidence: 92%
“…MTT. The results showed that the cell activity was reduced significantly after 4 h of hypoxia, and MiRNAs, known as small non-coding RNAs, play vital roles in many biological processes, regulate gene expressions at post-transcriptional level and interfere negatively with translation and RNA silencing [18]. Previous study [19] shows that miR-142-3p targets box 1, attenuating apoptosis of cardiomyocytes induced by H/R.…”
Section: Discussionmentioning
confidence: 92%
“…Of particular interest was the observation that the binding of miR-498 to FOXO3 3′-untranslated region increased its expression levels, an effect that is rare but not without precedent 77, 78 . Finally, overexpression of miR-142-5p in chicken primary myoblasts 79 and miR-155-5p in human foreskin fibroblasts 80 increased cell proliferation. This effect was mediated via a decrease in FOXO3 in both cell types.…”
Section: Microrna-mediated Regulation Of Foxo3mentioning
confidence: 93%
“…Thus, changes in the expression of interrelated miRNAs and target genes play a decisive role in controlling age-related alterations in muscle mass and function. In recent years, Illumina sequencing technology has been increasingly used to identify potential key interactions between miRNAs and mRNAs in the development of skeletal muscle [23][24][25]. However, miRNA-mRNA regulatory networks associated with the muscle growth, development and aging of sika deer have not been studied.…”
Section: Introductionmentioning
confidence: 99%